O desenvolvimento das competências socioemocionais na educação biocêntrica, na aprendizagem cooperativa e nos círculos de construção de paz a partir de uma narrativa autobiográfica - Holanda, Cristiane Carvalho (2020)
This research goal is to analyze the contributions of Biocentric Education, Cooperative Learning and Peace Building Circles towards the development of social and emotional skills based on my autobiographic narrative. The specific objectives are: to comprehend how can the Biocentric Education contribute towards the development of the affection, creativity and identifying emotions; Research how the Cooperative Learning strengthen the positive social interdependence, the self-management and autonomy of the students. Investigate how can the Peace Building Circles develop an empathetic communication and conflict resolution. One of the findings in this research was to identify that these practices are complementary and needed for a complete education. Based on the Life History and Formation approach, I made an autobiographical narrative of my involvement with teacher training building these new active methodologies. The aim is to write about the learning that came from the innovating experiences that have at their core the Freirean methodology and works with the Biocentric paradigm, cooperative and restorative from which I have worked on their building, disclosure and consolidation. This research helps to get a deeper understanding of those pedagogical approaches that seek to develop the following socio-emotional competencies such as: Extraversion, Openness, Agreeableness, Emotional Stability and self-management. Constructing a text contributing to the formation and (trans) formation of other people was a great challenge. During this process I could amplify my comprehensions on time and memory lenses. I rewrote my own history correlating with the theoretical contributions that have built these approaches and that have grounded my trajectory as a teacher in a permanent changing process. I wrote about my itinerary as a student and teacher who seeks to write from the heart but still connected to reason, Without losing the methodology rigor. I analyzed the most meaningful experiences that formed what I have been on the educational field, at the same time recognizing the great masters which I had the opportunity to work with and where the makers of those approaches. The writing about lived experiences is an invite towards a meeting with the sacred that is hidden in each one of us